Research on a Micro Flip Robot That Can Climb Stairs. (4th March 2016) - Wang, Jianzhong; Shi, Jiadong; Zhang, Shilong
Micro mobile robots (MMRs) can operate in rugged, narrow or dangerous regions; thus, they are widely used in numerous areas including surveillance, rescue and exploration. In urban environments, stairs are common obstacles, ones that such robots find difficult to manoeuvre over. The authors analysed the research status of MMRs, particularly in terms of difficulties when performing stair climbing and present a novel type of MMR called the micro flip robot (MFRobot). A support arm subassembly was added to the centre of a wheeled chassis; using this structure, the MFRobot can climb stairs when a flipping mode is utilized. Based on this structure, the authors established a kinematic model of the stair-climbing process and analysed the force conditions for the key status, contributing to the existing knowledge of robot design. An MFRobot prototype was produced and the stair-climbing experiments, as well as experiments on manoeuvring through rubble regions and slope surfaces, were conducted. The results show that the MFRobot can rapidly climb common stairs and can easily manoeuvre through a rubble region. The maximum slope angle the robot can climb was shown to be about 35° for concrete and wooden slope surfaces. In the case where the robot needed to be equipped with sensors, particularly a camera, the camera was equipped on the support arm of robot. The MFRobot prototype weighs 2.5 kg and is easily transportable. This structure can resolve contradictions between portability and performance in terms of overcoming obstacles; in addition, operational effectiveness can be improved using this structure.